Digital Pedagogical Innovations in English Language Education: A Systematic Literature Review - Khatimah, Husnul (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This systematic review aims to examine the incorporation of digital technologies in English language education, comparing it to conventional, non-digital approaches. The study investigates the effects of digital tools, including AI-driven tutoring systems, mobile learning platforms, and gamification, on improving language learning experiences. Subjects and Methods: The study utilized a structured approach in conducting a systematic literature review. Extensive analysis of current scholarly works on the integration of digital technologies in language education was conducted, focusing on studies that explore the use of AI tools, mobile platforms, and gamified learning. Results: The findings of this study indicate that digital technologies provide notable benefits to language learning. These include personalized learning paths, increased engagement through interactive content, and the opportunity to practice language skills in immersive, realistic scenarios. Despite these benefits, persistent challenges such as the digital divide, the necessity for teacher training, and the financial implications of adopting new technologies remain. These issues can hinder the full integration of digital technologies into language learning. Conclusions: The study concludes that digital innovations have a substantial impact on language learning outcomes. However, it is essential to emphasize that these technologies should be used in conjunction with, rather than as a substitute for, traditional methods. A hybrid approach combining the structured nature of traditional education with the interactive and adaptable qualities of digital methods has the potential to yield more comprehensive language learning outcomes.